From Collective Solidarity to Rational Participation: Transforming the Royongan Omah Tradition in Ngasinan Village, Indonesia - Wulandari, Dina Retno; Trinugraha, Yosafat Hermawan (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
This study aims to examine the transformation of Royongan Omah, a communal house-building tradition in Ngasinan Village, amid modernization and socio-economic changes. Traditionally, community participation in this practice was rooted in voluntary collective labor, driven by social solidarity and mutual aid. However, over time, participation has become increasingly selective and economically motivated. Employing a qualitative case study approach, this research collected data through passive participant observation, semi-structured interviews, and document analysis, which were analyzed using Miles and Huberman’s framework within Max Weber’s social action theory. The findings indicate that rationalization and shifting economic perspectives have significantly reshaped community participation in Royongan Omah. While participation was previously dominated by traditional, affective, and value-rational actions, it has now transitioned towards value-rational and instrumental-rational actions. Full community engagement—including labor, cognitive involvement, and material contributions—has declined, giving way to a more pragmatic approach that prioritizes skilled, paid labor for complex construction tasks. Despite the growing dominance of instrumental rationality, elements of traditional and affective rationality persist, demonstrating an ongoing negotiation between modern efficiency and cultural heritage. This study contributes to sociological discourse on modernization and cultural adaptation, highlighting how traditional cooperative labor systems evolve in response to socio-economic transformations.